2014
DOI: 10.1590/0104-6632.20140313s00002363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct and alternating current on the treatment of oily water in an electroflocculation process

Abstract: -In the direct current mode (DC), widely used in electroflocculation (EC), the formation of an impermeable oxide layer on the cathode causes the declining of the efficiency of this process. This disadvantage has been reduced by adopting alternating current (AC). In this study, the effects of AC and DC on operational parameters such as the removal of oils and greases (O&G), color and turbidity from oil-inwater (O/W) emulsions of the petroleum industry using aluminum electrodes were investigated. Removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
1
21
0
4
Order By: Relevance
“…Contrariwise, adopting AC can be the best solution for this problem thanks to the periodicity of this current that prevents the oxide layer formation and accelerates the reaction speed. and Cerqueira et al (2014) showed the importance of alternating current (AC) in the removal of pollutants by the electrocoagulation (EC) process through the dissolution of different electrode, such as Mg, Al, Fe and Zn. Achieving maximum pollutant removal in a minimum time was the common goal of all these researches.…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, adopting AC can be the best solution for this problem thanks to the periodicity of this current that prevents the oxide layer formation and accelerates the reaction speed. and Cerqueira et al (2014) showed the importance of alternating current (AC) in the removal of pollutants by the electrocoagulation (EC) process through the dissolution of different electrode, such as Mg, Al, Fe and Zn. Achieving maximum pollutant removal in a minimum time was the common goal of all these researches.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers, as Un et al (2009), Canizares et al (2007, Yang (2007), Bensadok et al (2008), Cerqueira et al (2014), and Karhu et al (2012), have reported high efficiency in removing chemical oxygen demand (COD), oil and grease (O&G), color, and turbidity, indicating that it is a promising alternative in treatment of oily emulsion for oil industry such as oilfield-produced water.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they had precipitated to the bottom [14][15][16]. Additionally, AC was applied to reduce corrosion of electrodes that can impact to efficiency loss of current transfer [17]. The product mixture of biodiesel and glycerol was prepared with the same procedure as mentioned in the previous section.…”
Section: Electrocoagulation Separation Processmentioning
confidence: 99%
“…Glycerol and other contaminants would receive charges between electrode points afterwards they were linked to large molecules and settled to the bottom [21]. Therefore, high voltage can excite electron movement around the electric field and several aluminum hydroxide species were produced [25].…”
Section: Effect Of Methyl Ester Contentmentioning
confidence: 99%